KARY A AL TERNATIF MAHASISWA (KAM) PENGEMBANGAN KEWIRAUSAHAAN PERCETAKAN SABLON MAHASISW A JURUSAN PLB FIP UNIVERSITAS NEGERI YOGYAKARTA - -, Haryanto (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
This program is aimed at givmg the students knowledge and practical skills through screen printing training in skill education subject in special education department. The objectives 6:f'the"program are (1) The students know about screen printing knowledge and theotY,'«~) -Have screen printing practical skills from setting, making klise, copying up to printing on the paper, plastic fabric, and solid matter, (3) Master in management and marketing, and (4) able to arrange a proposal for printing entrepreneurship. The methods of this program are: (l) Speech, giving information about screen printing knowledge and prospect, future chance, (2) Demonstrating the steps of screen printing from setting up to making the product, (3) Giving task, the students apply the screen printing knowledge they have from setting up to the printing on the various printing product, and (4) Discussion, discussing about the students difficulties in screen printing. The products outcomes of this program are: (1) Paper yields cards, calendars, small boxes, invitations cards, stickers, (2) Cloth yields T-shirt, flag, banners, headbands, and syals, (3) Plastic yields, stickers, plastic bags, stopmaps, labels, and (4) Solid matters yield souvenir, name plate, souvenir (the hung key). .Key words: entrepreneurship, and screen printing training.